Achieving academic promotion - Mahat, Marian; Tatebe, Jennifer (Emerald Publishing Limited, 2019)
This book demystifies the academic promotion process by bringing together international perspectives - both personal accounts and reflections on the structures and processes of promotion in different contexts - to help you understand the steps you can take at any stage of your career to move up the ladder.
Includes index.
Keywords: College teachers -- Promotions.; College teachers -- Vocational guidance.; Education -- Higher.; Colleges of higher education.; elektronické knihy; electronic books